2022
DOI: 10.3390/foods11030443
|View full text |Cite
|
Sign up to set email alerts
|

High Milk Somatic Cell Counts and Increased Teladorsagia Burdens Overshadow Non-Infection-Related Factors as Predictors of Fat and Protein Content of Bulk-Tank Raw Milk in Sheep and Goat Farms

Abstract: This paper presents the results of an extensive countrywide investigation performed in 325 dairy sheep flocks and 119 goat herds throughout Greece. The objectives of the study were (a) to investigate fat and protein content in the bulk-tank raw milk of small ruminant farms in Greece and (b) to identify factors potentially influencing that content and factors that can contribute to increased content. The mean fat/protein contents in bulk-tank raw milk of sheep and goats were 6.16 ± 0.05%/4.43 ± 0.01% and 4.77 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Before laboratory analysis, two 10 mL subsamples were created and processed; therefore, each separate test was performed four times (each one in different subsamples). Milk composition and somatic cell counting were performed within 4 h after collection on each of the four relevant subsamples, as previously detailed [ 9 , 10 , 11 ]. Moreover, milk samples were processed for total bacterial counts, and culturing was performed for isolation and identification of staphylococcal species as described previously [ 9 , 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before laboratory analysis, two 10 mL subsamples were created and processed; therefore, each separate test was performed four times (each one in different subsamples). Milk composition and somatic cell counting were performed within 4 h after collection on each of the four relevant subsamples, as previously detailed [ 9 , 10 , 11 ]. Moreover, milk samples were processed for total bacterial counts, and culturing was performed for isolation and identification of staphylococcal species as described previously [ 9 , 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis results for the two subsamples from each of the two milk samples collected from the bulk tank were averaged, then the two means were again averaged for the final result regarding each bulk-tank milk. For statistical analysis, the somatic cell counts were transformed to somatic cell scores and the total bacterial counts were transformed to log 10 as described previously [ 9 , 10 , 11 ]; the transformed data were used in the analyses. Differences were determined by using analysis of variance.…”
Section: Methodsmentioning
confidence: 99%
“…For epg counts, the value of 300 epg was defined, because in previous studies it had been considered as the threshold above which anthelmintic treatments should be performed [ 18 ] and was also found to be associated with the increased prevalence of subclinical mastitis [ 7 ] in dairy sheep in Greece. For the proportion of Teladorsagia spp., the threshold (63%) was defined, because in a recent study it emerged as a predictor affecting the composition of milk in dairy sheep [ 5 ]. Finally, for the proportion of H. contortus , the threshold (29%) was defined as the average proportion of the helminth in samples from all the untreated flocks in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…In dairy sheep production systems, previous publications have reported that gastrointestinal nematode parasitism can cause from 10 to 15% reduction in the milk yield of affected ewes [ 3 , 4 ]. Moreover, helminth infections have been found to be associated with reduced fat and protein contents in milk [ 4 , 5 ]. Additionally, these infections have been considered as potential risk factors for mastitis in ewes, as found in field (for trematodes [ 6 ] and nematodes [ 7 ]) or in experimental [ 8 ] studies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the visits in the farms, samples of bulk tank milk were collected for somatic cell counts, total bacterial counts and milk composition measurement. Full details of the collection and the processing of samples have been presented before [ 9 ].…”
Section: Methodsmentioning
confidence: 99%